Tables for the hydraulic design of pipes, sewers and channels. - Barr, D. I. H. (Thomas Telford, 1998)
This new edition again includes the extended range of pipe size that covers European standards as well as those for the newer materials now widely adopted in the UK. The book's main objective is to aid Colebrook-White assessments of resistance in such pipes and in a great variety of free-surface circumstances including large rivers.